Effect of posture-control insoles on function in children with cerebral palsy: Randomized controlled clinical trial - Neto, Hugo Pasini; Collange Grecco, Luanda Andre; Christovao, Thaluanna C. L.; Braun, Luiz Alfredo; Giannasi, Lilian Chrystiane [UNESP]; Inoue Salgado, Afonso Shiguemi; Franco de Moura, Renata Calhes; Camillo de Carvalho, Paulo de Tarso; Correa, Joao C. F.; Sampaio, Luciana M. M.; Galli, Manuela; Oliveira, Claudia Santos (Biomed Central Ltd., 2012)
Introduction: Cerebral palsy (CP) is a posture and movement disorder and different therapeutic modalities, such as the use of braces, have sought to favor selective motor control and muscle coordination in such patients. The aim of the proposed study is to determine the effect of the combination of posture-control insoles and ankle-foot orthoses (AFOs) improving functional limitation in children with CP.Methods/Design: The sample will be composed of 24 children with CP between four and 12 years of age. After the signing of the statement of informed consent, the children will be randomly allocated to two groups: a control group using AFOs alone and an experimental group using both posture-control insoles and AFOs. Evaluations will be performed on five occasions: without any accessory (insoles or AFOs), immediately after, one month after, six months after and one year after AFOs or insole and AFOs use. The evaluation will involve the analysis of gait, static and functional balance, mobility and hypertonia. The three-dimensional assessment of gait will involve the eight-camera SMART-D SMART-D 140 (R) system (BTS Engineering), two Kistler force plates (model 9286BA) and an eight-channel, wireless FREEEMG (R) electromyography (BTS Engineering). Static balance will be assessed using a Kistler force plate (model 9286BA). Clinical functional balance and mobility will be assessed using the Berg Balance Scale, Timed Up-and-Go Test and Six-Minute Walk Test. The posture-control insoles will be made of ethylene vinyl acetate, with thermal molding for fixation. The fixed orthoses will be made of polypropylene and attached to the ankle region (AFO). The results will be analyzed statistically, with the level significance set to 5% (p < 0.05).
Keywords: Cerebral palsy; Posture-control insoles; Ankle-foot orthosis; Electromyography; Gait; Stabilometry; Rehabilitation